Coming Out & In: A Collection of Steamy Queer Erotica - Simonsen, Betty Frank (Saga Egmont, 2023)
\'Coming Out & A Collection of Steamy Queer Erotica\' is a collection of sexy stories for the LGBTQI+ community. From horny stable boys and getting steamy in the sauna to friends with benefits, there\'s a story for every reader under the rainbow. Whether you\'re gay, lesbian, bisexual, pansexual, transgender or queer, these stories will definitely put you in the right mood.